Intralobar pulmonary sequestration complicated by a giant supplying artery aneurysm presenting for 9 years: a case report - Weng, Wei; Chi, Xinle; Liu, Ze; Chen, Weiqian; Wang, Shengze; Cai, Wenjie; Wu, Hai; Chen, Yaomeng (Frontiers in Surgery, 2025)
BackgroundThis article reports a case of a intralobar pulmonary sequestration (IPS) with a significantly large feeding artery aneurysm and shares the successful treatment experience.Case presentationA male was diagnosed with IPS combined with a feeding artery aneurysm approximately 74 mm × 61 mm in nine years ago but refused thoracotomy at that time. The patient presented this time due to an infection, and a CT scan revealed a significant increase in the lesion size to approximately 123 mm × 100 mm. After controlling the pulmonary inflammation, the patient underwent thoracoscopic ligation of the supplying artery, followed by an open chest excision of the sequestrated pulmonary aneurysm and left lower lobectomy, and the recovery post-surgery was very good.ConclusionWhen a sequestrated lung enlarges significantly, it is crucial to consider not only the conventional possibility of malignancy but also the rare coexistence of aneurysms. Thoracoscopic ligation of the supplying artery followed by open chest surgery is an effective treatment approach for IPS combined with a large feeding artery aneurysm.